Organic farming and greenhouse gas emissions: A longitudinal U.S. state-level study. (10th August 2018) - Squalli, Jay; Adamkiewicz, Gary
Abstract: Organic farming practices, focused on agro-ecological health, have long been centered on the idea that such approaches reduce resource intensity, improve soil health, reduce environmental burdens, and improve crop quality. These approaches can also mitigate climate change impacts. Our research examines the relationship between organic farming and greenhouse gas (GHG) emissions. Using U.S. state-level data over the 1997–2010 period, we estimate that a one percent increase in organic farming acreage could reduce GHG emissions by 0.049%. We also find that the impact of organic farming on methane and nitrous oxide emissions varies with the share of transportation output. Put in context, at the current shares of transportation output, organic farming is expected to mitigate methane and nitrous oxide emissions across most states. The connection between transportation and organic farming suggests that the environmental harm of transportation output embodied in organic food production might be too negligible to outweigh the environmental benefits of organic farming. The current study provides evidence supporting potential GHG mitigation benefits associated with organic food production. Policymakers and scientists can build on these results to further develop the evidence base and policies needed to quantify and maximize the benefits of adopting organic farming practices. Highlights: We examine the relationship between organic farming and greenhouse gas emissions. We make use of longitudinal U.S. state-level data over the 1997–2010 period. A one percent increase in organic farming acreage could reduce emissions by 0.049%. At current transportation output shares, growth in organic farming lowers emissions. Environmental gains from organic farming outweigh embodied harm from transportation.